Peran Perempuan Hindu dalam Situasi Pandemi Covid 19 - Diah Nirmala Dewi; Ni Wayan Yusi Armini; Anggy Paramitha Sari (Sanjiwani: Jurnal Filsafat, 2020)
A pandemic is an epidemic that has spread throughout the world, where in general this epidemic affects many humans / people. Epidemic is also a term that has been used for the purpose of knowing the sudden increase in the number of cases of disease in a population in a certain area. It needs to be discussed in the Covid-19 case for the first time caused by the corona virus which has spread in several countries since the end of last year, here the role of women can also take the role of men in various life arrangements. Women can earn a living like a man, but women can also be responsible for their nature to be a woman. From a Hindu point of view, Hindu women carry out their swadharmas with various roles in the family and society that can help their standard of living through the use of increasingly advanced technology.